Craniocerebral Maduramycosis: Masquerading as a Tumor - Renuka, Inuganti Venkata; Ramya, Chitturi; Chand, Velivela Kiran; Vidya, Tammina Mohana Sri; Premchand, Salumuri (Asian Journal of Neurosurgery, 2022)
Eumycetomas of craniocerebral are rare, and we report an extraordinary case of maduramycosis involving brain and skull bone in a middle-aged male who presented with complaints of headache, behavioral abnormalities, and memory disturbances for 3 months. Imaging showed a frontal lesion. It was mistaken for a tumor clinically and radiologically. Craniocerebral eumycetoma usually presents as a mass on the scalp with sinuses. Our case presented as a brain tumor without a soft tissue mass or discharging sinuses. It is essential to keep in mind this mode of presentation, and only a biopsy will aid in diagnosis.
Keywords: craniocerebral; maduramycosis; eumycetoma